Histopathological Changes due to Myxosporean Infectionin the Intestine of Fresh Water Goldfish (Carassius auratus) - Muchammad Yunus; Agus Sunarso; Agus Wijaya (The Indian Veterinary Journal, 2024)
This study was done to detect the presence of myxosporean parasite in the intestine of goldfish through intestinal histomorphological changes examination. Seventy five goldfish from culture ponds transferred live to the Parasitology laboratory. Gross observation and necropsy was done and intestinal tissues fixed for histopathological studies. No abnormalities were observed in body surfaces of all the collected goldfish. Histopathological changes indicated parasitic infection extending from villus to villus, originating from an initial infected area probably in the caecum. The myxosporean stages of an unidentified myxozoan attached to the intestinal brush and mucosa of fish which was named epi-epithelial myxosporean, and was observed for the first time in this tissue. The water temperatur of the Surabaya fish culture tanks were between 15 and 25°C throughout the year and the water temperature resembles that of tropical climate.